“Influencia de la violencia familiar en la autoestima y en el rendimiento académico en la I.E. “francisco izquierdo rios”, Octubre – Diciembre 2011” - Cisneros Pinedo, Rosa María (2011)
This research is descriptiva correlational, are carried out to determine the influence of family violence in self-esteem and academic performance in children aged 8-11 years. 1.E. "Francisco Izquierdo Ríos. October to December 2011. The sample was represented by 45 children who met the inclusion criteria. Surveys were conducted; autoelaborada, structured and lag notes to determine the types of family violence, self-esteem and academic achievement respectively., Which were systematized using the statistical package SPSS Microsoft Excel 2007 and Version 17.0. The results were: • The Family Violence does not influence self-esteem of children, since most of them have a high level of self-esteem, reflectad in a percentage of 79.3%. Also no effect on academic achievement because children have a level of performance expected accomplishment Provided (A = 11-16) which means they have passing grades, with percentage of 79.3%. • The presence of family violence in students from 8 to 11 years of 1 E Francisco Izquierdo Ríos is high with a rate of 64.4%, of which 100% presentad physical violence himself in this group is distinguished psychological violence 93.1 %, 37.9% sexual violence with violence and abandonment with 86.2%. • lt is established for this study that the Physical and Psychological Violence Violence is not the most influential in academic performance and self-esteem of students in the Educational lnstitution Francisco Izquierdo Rios. • For the study population the leve! of academic achievement prevails is provided with a percentage of 79.3%, and self-esteem is a high level with a percentage of 79.3%